Metabolic engineering of Clostridium acetobutylicum for gene essentiality studies - Akaluka, Cynthia Kelechi (2022)
In recent years the need to generate chemicals and fuels by sustainable routes has led to a resurgence of interest in exploiting butanol-producing species Clostridium acetobutylicum. It has a longstanding history in the commercial production of solvents in the so-called Acetone-Butanol-Ethanol (ABE) process. However, it has not operated on a commercial scale for several decades. A better understanding of the physiological factors that affect solvent production could have profound effects on the re-emergence of the ABE fermentation process on an industrial scale.